2018
DOI: 10.1002/hep4.1304
|View full text |Cite
|
Sign up to set email alerts
|

Development of Hepatic Steatosis After Chemotherapy for Non‐Hodgkin Lymphoma

Abstract: Nonalcoholic fatty liver disease is the most common liver disorder in the developed world. Although typically reflecting caloric overload, it can also be secondary to drug toxicity. We aimed to describe the incidence and risk factors for de novo steatosis during chemotherapy for non‐Hodgkin lymphoma (NHL). In this retrospective case‐control study, adult patients with NHL were treated with rituximab, cyclophosphamide, doxorubicin, prednisone, and vincristine (R‐CHOP) or R‐CHOP + etoposide (EPOCH‐R). Patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…We herein document the benefits of a low-calorie diet in a two-stage liver resection process. Furthermore, a study including two-stage liver resection combined with chemotherapy shows that chemotherapy produces steatosis but that it does not disappear much more than 3 weeks after stopping treatment [5]. Overall the available literature together with the present observation, support that the described 3-week hypocaloric hyper-protein diet can be used safely and efficiently in patients at risk of steatosis or with documented steatosis, and especially before surgery.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…We herein document the benefits of a low-calorie diet in a two-stage liver resection process. Furthermore, a study including two-stage liver resection combined with chemotherapy shows that chemotherapy produces steatosis but that it does not disappear much more than 3 weeks after stopping treatment [5]. Overall the available literature together with the present observation, support that the described 3-week hypocaloric hyper-protein diet can be used safely and efficiently in patients at risk of steatosis or with documented steatosis, and especially before surgery.…”
Section: Discussionsupporting
confidence: 73%
“…Nowadays, neoadjuvant or adjuvant treatments are routinely administered to patients undergoing surgery for colorectal cancer, including 5-fluoruracil, irinotecan, and oxaliplatin. Chemotherapy-associated steatosis (CAS) is therefore increasingly frequent, potentially limiting surgical strategies [5,6]. Although surgical techniques and patient care have improved in the recent years, hepatic steatosis is still recognized as an important risk factor for short and long-term complications and death after general surgery, and even more so after liver resection [7].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Hubert et al study showed that alcohol consumption and diabetes mellitus were associated with fatty liver disease and other demographic factors did not play a role (9). Ben-Yakov et al (11) showed the incidence of the fatty liver after chemotherapy was more in patients with higher BMI and pre-treatment history of hyperlipidemia than in other patients.…”
Section: Discussionmentioning
confidence: 98%
“…Ahn et al (16) reported that the frequency of fatty liver incidence was 25.8% in patients with breast cancer undergoing adjuvant chemotherapy with doxorubicin with cyclophosphamide. In another study, Ben-Yakov et al (11) examined the incidence of fatty liver in patients with non-Hodgkin's lymphoma treated with regimens containing rituximab, doxorubicin, cyclophosphamide, and prednisolone with or without etoposide, and the results showed that after treatment, up to 92% of the patients developed some degrees of hepatic steatosis.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, chemotherapy results in several systemic side effects such as gastrotoxicity, myelosuppression, nephrotoxicity, ototoxicity, hepatotoxicity, cardiotoxicity, neurotoxicity and allergic reactions. [2][3][4] Cisplatin is a metallic compound that possesses square planar geometry and is a widely used antitumor drug. It is dose-dependent, with its efficacy related closely to the concentration of the drug in the tumor.…”
Section: Introductionmentioning
confidence: 99%